Clinical Application of Standardized Cognitive Assessment Using fMRI. II. Verbal Fluency - Mark D. Allen; Alina K. Fong (Behavioural Neurology)
In this study, we describe an fMRI version of the verbal fluency test. This is the second in a series of fMRI adaptations of classical neuropsychological tests, for which normative samples of functional activation have been collected from unimpaired control subjects and structured in a manner that makes individual patient evaluation possible in terms of familiar z-score distributions. This fMRI protocol is shown to have strong convergent validity with the FAS phonemic fluency test and to elicit activation patterns highly consistent with a large body of previous neuroimaging studies of verbal fluency. We also present a case study, in which we report concurrent data from a patient with selective deficits in verbal processing, using both conventional neuropsychological and fMRI approaches. These analyses reveal striking correspondences between the deficits present in this patient on cognitive performance tests and the equally selective patterns of deviation present in his fMRI data.